Students’ perceptions of careers: the influence of academic performance and self efficacy in Kisumu Municipality - Ajowi, Jack Odongo; Obura, Caroline Atieno (European Scientific Journal, 2012)
The perceptions of career aspirations of secondary school students in Kisumu Municipality had not been clearly understood. It was hypothesized that students’ performance in examinations and self-efficacy could be related to students’ perceptions of career aspirations. The study therefore examined the perceptions of career aspirations of secondary school students in Kisumu Municipality. Although similar studies had been carried out elsewhere, no study conducted in Kisumu Municipality had specifically focused on perceptions of career aspirations of secondary school students. The previous studies on careers had concentrated mainly on post-secondary school students who had already made career choices. The present study therefore examined students’ aspirations before they made choices. The purpose of the study was to establish the factors related to perceptions of career aspirations of secondary school students in Kisumu Municipality. The findings of the study will hopefully contribute to knowledge in the area of gender studies and career guidance. The study used descriptive survey design. The study population consisted of 1596 students and 25 career guidance teachers in Kisumu Municipality. Purposive sampling was used to select 8 public secondary schools that were likely to have a combination of students with different abilities and therefore likely to have different career aspirations. Stratified random sampling technique was used to select a representative sample of 237 male, 238 female students and 8 teachers heading career guidance department in the selected schools. Data were collected using student and teacher questionnaires and interview schedules. Descriptive and chi-square statistics were used to analyze the relationships between the selected factors and career aspirations of students. The relationship between students’ career aspirations and performance in examinations and level of self-efficacy were found to be statistically significant.